Quality of life in paediatric population from 8 to 12 years with asthma - Gabriela Maldonado Guzmán (Fundación para el Desarrollo de la Enfermería, 2007)
The quality of life in patients with chronic problems as the asthma, at present performs major importance in view of the increase of the life expectancy. Nevertheless, often this one does not accompany of conditions biopsicosocial acceptable, that allow to the person to enjoy good emotional condition, as well as the accomplishment of his or her physical, social and school activities. The objective of this study is to know the quality life of the physical, emotional, social, and scholar valuation. Methodology: This study was realized with a number of 124 children sample in ages of 8 to 12 years old with asthma diagnostic.Results: The most damage aspects within quality life dimension were run, work out; lower energy and feeling pain. Emotional aspects were be worried about the future and insomnia, respect to social dimension the problem was children can't keep in the same condition than others while they are playing; and about school dimension the problem was school absence because of their need of going to the doctor or hospital. Discussion: The aspects of the physical dimension that were more affected to are the follow: run, to do exercise, to have little energy, and to feel pain. Both first ones have relation with the (reported) by the Spanish Society of Neumología and Paediatrics (s.f.), Where they brought (reported) that the children more affected because of the asthma to were those that run and to do exercise. With regard to having little energy and feeling pain, this can owe to persistent accesses of cough, that really they cause weakness and pain in the thoracic box. Conclusions: These results suggest that it is important to stimulate the self-esteem of the children who endure asthma across his participation in an equipment or group.